Institutional conditions of development of agro-industrial complex in Kazakhstan and Mongolia - Byambayar, Yadamsuren; Hadys, Batyrbek (BUKETOV BUSINESS REVIEW, 2017)
In the article institutional conditions of development of agro-industrial complex in Kazakhstan and Mongolia at the present stage are considered. Key parameters of development of agriculture of two countries in the directions - crop production and livestock production - are analyzed. It is established that conditions of development of agro-industrial complexes of Mongolia and Kazakhstan on highlights are identical; similar climatic conditions of two countries, their variety is caused by considerable potential opportunities for development of livestock production. However there is a number of factors which exert negative impact on development of agro-industrial complex of two countries. First of all, it is problems of institutional character which create unequal conditions of border relationship of two countries. It should be noted the most developed state institutes of development of agro-industrial complex of Kazakhstan represented by «KazAgro» Holding which experience of functioning will be useful to institutional development of agro-industrial complex of Mongolia.